Biomass solid waste furfural residue combustion method

By mixing high-water furfural slag with low-water water absorbent, water transfer and combustion are achieved, and the problems of slow combustion speed and bonding of furfural slag are solved, and the combustion rate and recycling rate are improved.

CN119912988AActive Publication Date: 2025-05-02BEIJING AOKE RUIFENG NEW ENERGY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510159463.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-05-02
Estimated Expiration
2045-02-13

AI Technical Summary

Technical Problem

The burning rate of furfural slag is low and the combustion speed is slow. It is easy to form silicates with low melting points during the combustion of the boiler, resulting in bonding and agglomeration.

Method used

By mixing high-water furfural slag with low-water water absorbents (a mixture of calcium-based bentonite and sodium-based bentonite), water transfer is achieved, the moisture content of furfural slag is reduced, followed by sieving and combustion, and drying and recycling using the waste heat of flue gas.

Benefits of technology

The combustion rate and combustion speed of furfural slag are improved, bonding and agglomeration are avoided, and efficient recycling of low-water water absorbents is achieved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a biomass solid waste furfural residue combustion method, which comprises the following steps: adding bentonite into furfural residues, uniformly mixing, stacking, sieving with a 200-mesh sieve, taking oversize products as furfural residues with low moisture content, taking undersize products as bentonite after water absorption, and drying, recovering and recycling the bentonite after water absorption. Calcium bentonite and sodium bentonite are added into furfural residues according to a certain ratio by utilizing the characteristic that calcium bentonite and sodium bentonite have very strong water absorption, so that moisture in the furfural residues can be adsorbed, the low-moisture furfural residues are obtained, the moisture content in the furfural residues is reduced to 30% or below, and the furfural residues can be directly used as biomass fuel without being dried.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomass fuel preparation, and more specifically to a method for burning furfural residue of biomass solid waste. Background Art

[0002] Furfural residue is a by-product of furfural (furan formaldehyde) produced by hydrolysis of corn cobs. It contains a large amount of lignin, cellulose, etc. It has a high secondary utilization value and can be used as a biomass fuel.

[0003] However, the volume of furfural slag is large (average particle size is about 15mm) and the moisture content is high (30-40%), which will result in a low burnout rate and slow combustion speed. In addition, the furfural slag has a high content of alkali metals such as potassium and sodium, which easily forms low-melting silicates during boiler combustion, resulting in adhesion and agglomeration on the bed surface.

[0004] The current treatment method is to increase the combustion speed and burnout rate by reducing the moisture content and controlling the particle size distribution range. The conventional method of reducing the moisture content is mostly baking and heating to reduce the moisture content of furfural slag to less than 30%. Summary of the invention

[0005] To this end, the technical problem to be solved by the present invention is to provide a method for burning furfural slag from biomass solid waste, so as to solve the problems of low burnout rate, slow combustion speed and compacted particles of furfural slag in the prior art.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for burning furfural slag from biomass solid waste comprises the following steps: (1) Mixing: Mix high-moisture furfural residue with low-moisture absorbent; (2) Moisture transfer: transfer part of the water in the high-moisture furfural residue to the low-moisture water absorbent to obtain a mixture of low-moisture furfural residue and high-moisture water absorbent; (3) Screening: Screen the mixture of low-moisture furfural residue and high-moisture water absorbent, the material on the screen is the low-moisture furfural residue, and the material under the screen is the high-moisture water absorbent; (4) Combustion: compressing low-moisture furfural slag into biomass fuel for combustion, or directly burning low-moisture furfural slag bulk as biomass fuel; (5) Drying and recovery: The high-moisture water absorbent obtained in step (3) is dried using the waste heat of the flue gas generated by the combustion of the low-moisture furfural slag in step (4), and then returned to step (1) as the low-moisture water absorbent.

[0007] In the above-mentioned biomass solid waste furfural slag combustion method, in step (1): the low-moisture water absorbent is a mixture of calcium-based bentonite and sodium-based bentonite, and the water absorption expansion multiple of the calcium-based bentonite is smaller than the water absorption expansion multiple of the sodium-based bentonite.

[0008] In the above-mentioned biomass solid waste furfural slag combustion method, in step (1): in the low-moisture water absorbent, the mass ratio of calcium-based bentonite to sodium-based bentonite is 2 to 3:1.

[0009] In the above-mentioned biomass solid waste furfural slag combustion method, the calcium-based bentonite is carboxymethyl starch-modified calcium-based bentonite.

[0010] The above-mentioned biomass solid waste furfural residue combustion method and the preparation method of carboxymethyl starch modified calcium-based bentonite are as follows: Step (1-1), adding sodium carboxymethyl starch to acetic acid, stirring thoroughly, adding water, adjusting the pH value to 2 with hydrochloric acid solution and continuing stirring; then performing solid-liquid separation, washing the precipitate obtained by solid-liquid separation with anhydrous ethanol and drying to obtain carboxymethyl starch; Step (1-2), adding carboxymethyl starch and calcium bentonite to an ethanol solution, then adding hexadecyltrimethylammonium bromide and ammonium molybdate and stirring to mix, and then placing in a water bath and stirring to allow for a full reaction; after the water bath ends, filtering and drying to obtain carboxymethyl starch modified calcium bentonite.

[0011] The above-mentioned biomass solid waste furfural slag combustion method, in step (1-1), the mass volume ratio of sodium carboxymethyl starch to acetic acid is (0.75-1.0) g / mL; the volume ratio of water to acetic acid is (0.75-1.0):1; the concentration of the hydrochloric acid solution is 1-1.5 mol / L, the pH is adjusted to 2 and stirring is continued for 20-30 minutes; after solid-liquid separation, the precipitate is washed with anhydrous ethanol for 2-3 times, and the drying condition is dried at 60°C for 1-2 hours; the dried solid product is passed through a 200-mesh sieve, and the sieve-through is the carboxymethyl starch; In step (1-2), the mass ratio of carboxymethyl starch to calcium bentonite is 1:10-20; the mass volume ratio of calcium bentonite to ethanol solution is (0.15-0.50) g / mL, and the ethanol solution is prepared by mixing water and anhydrous ethanol in a volume ratio of (1-3):1; the amount of hexadecyltrimethylammonium bromide added is 1-2% of the total mass of carboxymethyl starch and calcium bentonite, and the amount of ammonium molybdate added is 0.5-1.0% of the total mass of carboxymethyl starch and calcium bentonite; the water bath stirring conditions are: stirring in a water bath at 50-60° C. for 2-3 h; and the drying conditions are drying at 80-90° C. for 6-10 h.

[0012] The above-mentioned biomass solid waste furfural slag combustion method, in step (1-1), the mass volume ratio of sodium carboxymethyl starch to acetic acid is 1.0g / mL; the volume ratio of water to acetic acid is 0.75:1; the concentration of the hydrochloric acid solution is 1.0mo / L, the pH is adjusted to 2 and stirring is continued for 30min; after solid-liquid separation, the precipitate is washed 3 times with anhydrous ethanol, and the drying condition is: drying at 60°C for 1.5h; the dried solid product is passed through a 200-mesh sieve, and the sieve-through is the carboxymethyl starch; In step (1-2), the mass ratio of carboxymethyl starch to calcium bentonite is 1:10; the mass volume ratio of calcium bentonite to ethanol solution is 0.20 g / mL, and the ethanol solution is prepared by mixing water and anhydrous ethanol in a volume ratio of 2:1; the amount of cetyltrimethylammonium bromide added is 1.0% of the total mass of carboxymethyl starch and calcium bentonite, and the amount of ammonium molybdate added is 0.5% of the total mass of carboxymethyl starch and calcium bentonite; the water bath stirring conditions are: stirring in a water bath at 60° C. for 2 h; and the drying conditions are: drying at 80° C. for 4 h.

[0013] In the above-mentioned biomass solid waste furfural slag combustion method, in step (1): the amount of low-moisture water absorbent added is 15-20% of the mass of high-moisture furfural slag; the particle size of furfural slag is controlled to be 0.5-1 mm; the low-moisture water absorbent is passed through a 400-mesh sieve. When preparing the low-moisture water absorbent, firstly, calcium-based bentonite and sodium-based bentonite are passed through a 400-mesh sieve respectively, and then the sieve under the calcium-based bentonite and the sieve under the sodium-based bentonite are mixed to form the low-moisture water absorbent.

[0014] In the above-mentioned method for burning furfural residues of biomass solid waste, in step (3), the mixture of low-moisture furfural residues and high-moisture water absorbent is sieved through a 200-mesh sieve.

[0015] In the above-mentioned method for burning furfural slag from biomass solid waste, in step (2), the method for transferring moisture is as follows: the stacking time at room temperature is 3-4 days.

[0016] In the above-mentioned method for burning furfural slag of biomass solid waste, in step (4): the calcium-based bentonite and sodium-based bentonite remaining in the low-moisture furfural slag can effectively reduce the adhesion of biomass combustion ash particles on the surface of the fluidized bed at high temperature.

[0017] The technical solution of the present invention achieves the following beneficial technical effects: 1. The present invention utilizes the strong water absorption property of calcium-based bentonite and sodium-based bentonite, and adds them to furfural residue in a certain proportion, thereby absorbing the moisture in the furfural residue to obtain furfural residue with low moisture content, and reducing the moisture content in the furfural residue to below 30%, so that the furfural residue can be directly used as a biomass fuel without drying.

[0018] 2. In the present invention, calcium bentonite and sodium bentonite are selected as low-moisture water absorbents because: calcium bentonite has a small water absorption capacity, which is no more than 200% at most, and its expansion multiple is only several to more than ten times, and its water absorption speed is fast, and the colloid price is about 60%; sodium bentonite has a large water absorption capacity, which is up to more than 500%, and its expansion multiple is as high as 20 to 30 times, but its water absorption speed is slow, the time is long, and the colloid price is as high as 100%. According to the characteristics of calcium-based bentonite and sodium-based bentonite, the proportion of calcium-based bentonite and sodium-based bentonite is reasonably controlled, and a certain proportion of sodium-based bentonite and calcium-based bentonite are uniformly mixed as low-moisture absorbents for stacking when the furfural slag is discharged, so as to achieve the purpose of naturally reducing the moisture content of the furfural slag. Therefore, the method of the present invention realizes the transfer of moisture in a large-volume material with poor thermal conductivity (high-moisture furfural slag) to a small-volume material with good thermal conductivity (a mixture of low-moisture absorbent-calcium-based bentonite and sodium-based bentonite), and eliminates the complicated process of drying the furfural slag before burning. Only low-temperature flue gas is needed to dry the sodium-based bentonite and calcium-based bentonite with small volume and good thermal conductivity.

[0019] 3. Since sodium-based bentonite has the characteristics of slow water absorption and high colloid price, while calcium-based bentonite has the characteristics of fast water absorption and low colloid price, after mixing the two with furfural residue in a specific ratio, calcium-based bentonite can quickly reduce the moisture content at the interface of bentonite-furfural residue, thereby effectively avoiding the adhesion or adhesion between sodium-based bentonite and furfural residue after water absorption when the moisture content of furfural residue is high in the initial stage, thereby avoiding the problem of difficulty in recycling most of the sodium-based bentonite after water absorption.

[0020] 4. Calcium bentonite can quickly absorb water to saturation and expand to several to dozens of times its own volume, while the particle size of furfural slag is usually millimeter-level. Therefore, sodium bentonite with smaller particle size can be filled in "small gaps formed between calcium bentonite particles or between calcium bentonite particles and furfural slag particles" when initially absorbing water, further preventing the sodium bentonite from adhering or sticking to the furfural slag in the early stage of water absorption; as the sodium bentonite slowly absorbs water and expands dozens of times and gradually fills these small gaps, although the contact area between the sodium bentonite particles and the furfural slag increases, the contact area ratio is relatively small relative to the total surface area of ​​the sodium bentonite after expansion, and the adhesion or sticking force is much smaller than the gravity of the sodium bentonite after expansion. Moreover, the moisture content of the furfural slag is further reduced at this time, so that the furfural slag can be easily separated and recycled by screening to separate the sodium bentonite and calcium bentonite before combustion, and the overall recovery rate of sodium bentonite and calcium bentonite can reach 84.7%.

[0021] 5. Sodium bentonite and calcium bentonite have the property of reversible dehydration and rehydration, and compared with furfural slag, sodium bentonite and calcium bentonite have strong thermal conductivity. By using the waste heat of flue gas to dry sodium bentonite and calcium bentonite, the material can be quickly heated from the outside to the inside; the bound water adsorbed by sodium bentonite and calcium bentonite can be lost within 60 minutes at 100-200°C. Therefore, the present invention uses the waste heat of low-temperature flue gas (below 200°C) generated by the combustion of furfural slag to quickly dry and dehydrate the sodium bentonite and calcium bentonite after absorbing water and then continue to put them into use. It is only necessary to replenish the sodium bentonite and calcium bentonite lost in the circulation process to realize the circulation of the furfural slag combustion process.

[0022] 6. The present invention uses carboxymethyl starch to modify calcium-based bentonite. The carboxymethyl starch-modified calcium-based bentonite prepared by the method of the present invention is mixed with sodium-based bentonite and then mixed with furfural residue as a low-moisture water absorbent. The recovery rate of screening after water transfer is significantly improved, and its water absorption capacity is basically unchanged after drying in the low-temperature flue gas generated by the combustion of furfural residue, and can be used repeatedly. The method of modifying calcium-based bentonite with carboxymethyl starch of the present invention can make the hydrophobic end of carboxymethyl starch firmly adsorbed on the surface of calcium-based bentonite, and its hydrophilic end can combine with water molecules in furfural residue, thereby establishing a bridge connection between calcium-based bentonite and furfural residue, significantly improving the affinity of calcium-based bentonite and furfural residue, and effectively preventing sodium-based bentonite with high colloid value from adhering to furfural residue, so that the overall recovery rate of sodium-based bentonite and calcium-based bentonite reaches 92.5%. DETAILED DESCRIPTION

[0023] Example 1 The method for burning furfural slag from biomass solid waste in this embodiment comprises the following steps: (1) Mixing: 1000 g of high-moisture furfural residue with a moisture content of 40% and 150 g of a low-moisture water absorbent are mixed evenly; the low-moisture water absorbent is prepared by mixing 100 g of calcium-based bentonite and 50 g of sodium-based bentonite, and the water absorption expansion multiple of the calcium-based bentonite is smaller than that of the sodium-based bentonite; The preparation method of the low-moisture water absorbent is as follows: firstly, calcium-based bentonite and sodium-based bentonite are respectively passed through a 400-mesh sieve, and then 100 g of the sieve under the calcium-based bentonite and 50 g of the sieve under the sodium-based bentonite are mixed to obtain the low-moisture water absorbent; In this embodiment, the particle size of furfural residue is controlled within the range of 0.5 to 1 mm; (2) Moisture transfer: The mixture of high-moisture furfural residue and low-moisture water absorbent is piled up at room temperature for 3 days to allow the water in the high-moisture furfural residue to be fully transferred to the low-moisture water absorbent, thereby obtaining a mixture of low-moisture furfural residue and high-moisture water absorbent; (3) Screening: The mixture of low-moisture furfural residue and high-moisture water absorbent is screened through a 200-mesh sieve. The material on the sieve is low-moisture furfural residue (the moisture content of which is 21% after testing), and the material under the sieve is high-moisture water absorbent - a mixture of calcium-based bentonite and sodium-based bentonite after water absorption and expansion; (4) Combustion: compressing low-moisture furfural slag into biomass fuel for combustion, or directly burning low-moisture furfural slag bulk as biomass fuel; (5) Drying and recovery: The high-moisture water absorbent obtained in step (3) is dried for 60 min using the flue gas waste heat (less than 200° C.) generated by the combustion of the low-moisture furfural slag in step (4) to obtain 127 g of a mixture of calcium-based bentonite and sodium-based bentonite, which is then returned to step (1) as a low-moisture water absorbent after drying.

[0024] In this embodiment, the overall recovery rate of the low-moisture water absorbents - sodium bentonite and calcium bentonite is 84.7%. In step (4), the screened material obtained by sieving contains a small amount of high-moisture water absorbent (calcium bentonite and sodium bentonite) in addition to the furfural residue. These bentonites can effectively reduce the adhesion of biomass combustion ash particles on the surface of the fluidized bed under high combustion temperature.

[0025] Example 2 The method for burning furfural slag from biomass solid waste in this embodiment comprises the following steps: (1) Mixing: 1000 g of high-moisture furfural residue with a moisture content of 45% and 200 g of a low-moisture water absorbent are mixed evenly; the low-moisture water absorbent is prepared by mixing 150 g of carboxymethyl starch-modified calcium-based bentonite and 50 g of sodium-based bentonite, and the water absorption expansion multiple of the calcium-based bentonite is smaller than that of the sodium-based bentonite; The preparation method of the low-moisture water absorbent is as follows: first, carboxymethyl starch-modified calcium-based bentonite and sodium-based bentonite are respectively passed through a 400-mesh sieve, and then 150 g of the carboxymethyl starch-modified calcium-based bentonite and 50 g of the sodium-based bentonite are mixed to obtain the low-moisture water absorbent; In this embodiment, the particle size of furfural residue is controlled within the range of 0.5 to 1 mm; (2) Moisture transfer: The mixture of high-moisture furfural residue and low-moisture water absorbent is piled up at room temperature for 3 days to allow the water in the high-moisture furfural residue to be fully transferred to the low-moisture water absorbent, thereby obtaining a mixture of low-moisture furfural residue and high-moisture water absorbent; (3) Screening: The mixture of low-moisture furfural residue and high-moisture water absorbent is screened through a 200-mesh sieve. The material on the sieve is low-moisture furfural residue (the moisture content of which is 20% after testing), and the material under the sieve is high-moisture water absorbent - a mixture of carboxymethyl starch-modified calcium-based bentonite and sodium-based bentonite after water absorption and expansion; (4) Combustion: compressing low-moisture furfural slag into biomass fuel for combustion, or directly burning low-moisture furfural slag bulk as biomass fuel; (5) Drying and recovery: The high-moisture water absorbent obtained in step (3) is dried for 60 min using the flue gas waste heat (less than 200° C.) generated by the combustion of the low-moisture furfural slag in step (4) to obtain 185 g of a mixture of carboxymethyl starch-modified calcium-based bentonite and sodium-based bentonite, which is then returned to step (1) as a low-moisture water absorbent after drying.

[0026] In step (1) of this embodiment, the preparation method of carboxymethyl starch modified calcium-based bentonite is: Step (1-1), 20 g of sodium carboxymethyl starch is added to 20 mL of acetic acid, and then 15 mL of water is added, and the pH value is adjusted to 2 with 1 mol / L hydrochloric acid, and stirring is continued for 25 min. The mixture is washed with ethanol three times and filtered, dried at 60° C. for 1.5 h, and sieved through a 200-mesh sieve to obtain carboxymethyl starch.

[0027] Step (1-2), 20 g of carboxymethyl starch and 200 g of calcium-based bentonite are added to 1000 mL of ethanol solution (the ethanol solution is prepared by mixing water and anhydrous ethanol in a volume ratio of 2:1), and then 2.2 g of hexadecyltrimethylammonium bromide and 1.1 g of ammonium molybdate are added, stirred in a water bath at 60° C. for 2 h, filtered and dried at 80° C. for 4 h to obtain carboxymethyl starch-modified calcium-based bentonite.

[0028] In this embodiment, the overall recovery rate of the low-moisture water absorbent - carboxymethyl starch modified calcium-based bentonite and sodium-based bentonite is 92.5%.

[0029] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of this patent application.

Claims

1. A method for burning furfural slag from biomass solid waste, characterized in that: The steps include: (1) Mixing: Mix high-moisture furfural residue with low-moisture absorbent; (2) Moisture transfer: transfer part of the water in the high-moisture furfural residue to the low-moisture water absorbent to obtain a mixture of low-moisture furfural residue and high-moisture water absorbent; (3) Screening: Screen the mixture of low-moisture furfural residue and high-moisture water absorbent, the material on the screen is the low-moisture furfural residue, and the material under the screen is the high-moisture water absorbent; (4) Combustion: compressing low-moisture furfural slag into biomass fuel for combustion, or directly burning low-moisture furfural slag bulk as biomass fuel; (5) Drying and recovery: The high-moisture water absorbent obtained in step (3) is dried using the waste heat of the flue gas generated by the combustion of the low-moisture furfural slag in step (4), and the dried product is returned to step (1) as a low-moisture water absorbent.

2. The biomass solid waste furfural slag combustion method according to claim 1, characterized in that: In step (1): the low-moisture absorbent is a mixture of calcium-based bentonite and sodium-based bentonite, and the water absorption expansion multiple of the calcium-based bentonite is smaller than the water absorption expansion multiple of the sodium-based bentonite.

3. The biomass solid waste furfural slag combustion method according to claim 2, characterized in that: In step (1): in the low-moisture absorbent, the mass ratio of calcium-based bentonite to sodium-based bentonite is 2 to 3:

1.

4. The biomass solid waste furfural slag combustion method according to claim 2, characterized in that: Calcium bentonite is carboxymethyl starch modified calcium bentonite.

5. The biomass solid waste furfural slag combustion method according to claim 4, characterized in that: The preparation method of carboxymethyl starch modified calcium-based bentonite is: Step (1-1), adding sodium carboxymethyl starch to acetic acid, stirring thoroughly, adding water, adjusting the pH value to 2 with hydrochloric acid solution and continuing stirring; then performing solid-liquid separation, washing the precipitate obtained by solid-liquid separation with anhydrous ethanol and drying to obtain carboxymethyl starch; Step (1-2), adding carboxymethyl starch and calcium bentonite to an ethanol solution, then adding hexadecyltrimethylammonium bromide and ammonium molybdate and stirring to mix, and then placing in a water bath and stirring to allow for a full reaction; after the water bath ends, filtering and drying to obtain carboxymethyl starch modified calcium bentonite.

6. The method for burning furfural slag from biomass solid waste according to claim 5, characterized in that: In step (1-1), the mass volume ratio of sodium carboxymethyl starch to acetic acid is (0.75-1.0) g / mL; the volume ratio of water to acetic acid is (0.75-1.0):1; the concentration of the hydrochloric acid solution is 1-1.5 mol / L, the pH is adjusted to 2 and stirring is continued for 20-30 min; after solid-liquid separation, the precipitate is washed 2-3 times with anhydrous ethanol and dried at 60° C. for 1-2 h; the dried solid product is sieved through a 200-mesh sieve, and the sieved product is carboxymethyl starch; In step (1-2), the mass ratio of carboxymethyl starch to calcium bentonite is 1:10-20; the mass volume ratio of calcium bentonite to ethanol solution is (0.15-0.50) g / mL, and the ethanol solution is prepared by mixing water and anhydrous ethanol in a volume ratio of (1-3):1; the amount of hexadecyltrimethylammonium bromide added is 1-2% of the total mass of carboxymethyl starch and calcium bentonite, and the amount of ammonium molybdate added is 0.5-1.0% of the total mass of carboxymethyl starch and calcium bentonite; the water bath stirring conditions are: stirring in a water bath at 50-60° C. for 2-3 h; and the drying conditions are drying at 80-90° C. for 4-8 h.

7. The method for burning furfural slag from biomass solid waste according to claim 6, characterized in that: In step (1-1), the mass volume ratio of sodium carboxymethyl starch to acetic acid is 1.0 g / mL; the volume ratio of water to acetic acid is 0.75:1; the concentration of the hydrochloric acid solution is 1.0 mol / L, the pH is adjusted to 2 and stirring is continued for 25 minutes; After solid-liquid separation, the precipitate was washed with anhydrous ethanol for 3 times and dried at 60°C for 1.5 hours. The dried solid product was sieved with a 200-mesh sieve, and the sieved product was carboxymethyl starch. In step (1-2), the mass ratio of carboxymethyl starch to calcium bentonite is 1:10; the mass volume ratio of calcium bentonite to ethanol solution is 0.20 g / mL, and the ethanol solution is prepared by mixing water and anhydrous ethanol in a volume ratio of 2:1; the amount of cetyltrimethylammonium bromide added is 1.0% of the total mass of carboxymethyl starch and calcium bentonite, and the amount of ammonium molybdate added is 0.5% of the total mass of carboxymethyl starch and calcium bentonite; the water bath stirring conditions are: stirring in a water bath at 60° C. for 2 h; and the drying conditions are: drying at 80° C. for 4 h.

8. The method for burning furfural slag from biomass solid waste according to any one of claims 1 to 7, characterized in that: In step (1): the amount of low-moisture water absorbent added is 15-20% of the mass of high-moisture furfural residue; the particle size of furfural residue is controlled to be 0.5-1 mm; and the low-moisture water absorbent is sieved through a 400-mesh sieve.

9. The method for burning furfural slag from biomass solid waste according to claim 8, characterized in that: In step (3), the mixture of low-moisture furfural residue and high-moisture water absorbent is screened through a 200-mesh screen.

10. The method for burning furfural slag from biomass solid waste according to claim 9, characterized in that: In step (2), the method of moisture transfer is: stacking a mixture of high-moisture furfural residue and low-moisture water absorbent at room temperature for 3 to 4 days.

Citation Information

Patent Citations

  • Kitchen waste energy treatment process

    CN104646391A

  • Preparation method for biomass granular fuel

    CN104893779A

  • Furfural residue light through hole ceramsite

    CN106083152A

  • Oil sludge fuel brick and preparation method thereof

    CN110257125A

  • Treatment process of biomass furfural residues

    CN116948719A